Absence seizure susceptibility correlates with pre-ictal β oscillations. Issue 4 (November 2016) - Sorokin, Jordan M.; Paz, Jeanne T.; Huguenard, John R.
Highlights: Spontaneous SWDs in WAGRij rats correlate with pre-ictal 20–40 Hz (β) power. Thalamocortical (TC) firing rate decreases prior to spontaneous SWD onset. Induced SWDs are more likely when preceded by higher β power. TC firing rate displays similar dynamics between induced and spontaneous SWDs. Abstract: Absence seizures are generalized, cortico-thalamo-cortical (CTC) high power electroencephalographic (EEG) or electrocorticographic (ECoG) events that initiate and terminate suddenly. ECoG recordings of absence seizures in animal models of genetic absence epilepsy show a sudden spike-wave-discharge (SWD) onset that rapidly emerges from normal ECoG activity. However, given that absence seizures occur most often during periods of drowsiness or quiet wakefulness, we wondered whether SWD onset correlates with pre-ictal changes in network activity. To address this, we analyzed ECoG recordings of both spontaneous and induced SWDs in rats with genetic absence epilepsy. We discovered that the duration and intensity of spontaneous SWDs positively correlate with pre-ictal 20–40 Hz (β) spectral power and negatively correlate with 4–7 Hz (Ø) power. In addition, the output of thalamocortical neurons decreases within the same pre-ictal window of time. In separate experiments we found that the propensity for SWD induction was correlated with pre-ictal β power. These results argue that CTC networks undergo a pre-seizure state transition, possibly due to a functional reorganization of cortical microcircuits, which leads to the generation of absence seizures.